Contribuições da terapia ocupacional para a introdução de recursos de comunicação alternativa no atendimento educacional especializado - Pratti, Gabriella de Oliveira (Universidade Federal de São Carlos, 2021)
Communication is one of the main resources responsible for the development of the individual, being the main way for sending and receiving messages, recording facts, expressing feelings, among others. Studies show that non-existent or inefficient communication directly impacts the main daily tasks, access to services, learning of new skills, and social involvement. One of the areas of Assistive Technology, Alternative and Extended Communication (CAA) aims to minimize the effects of communicative limitations, with the same effectiveness of the spoken language.This study aims to present my academic trajectory within Assistive Technology, more specifically in Alternative Communication, during graduation in occupational therapy, through two experiences and their products. These studies are about the understanding process of the introduction of pictographic communication systems and resources, with students with cerebral palsy in the school context, in a municipality in the interior of São Paulo, more specifically in Special Education spaces.The first study is the participation in extension projects carried out in a special education institution, in 2018 and 2019. The second is a technological initiation in a school of municipal education inserted in the actions of the Specialized Educational Service. The derived products resulted in experience reports and reports, in addition to presentations at the Brazilian Congress of Alternative Communication and an Occupational Therapy Journey. All these experiences provided me with reflections about the daily life and all the different activities inserted in it, the school environment as a powerful space for social inclusion and a deeper understanding of individuals and their social and health relationships, so inherent in the perspectives of Occupational Therapy.
Contributions of occupational therapy to the introduction of alternative communication devices in specialized educational care
Keywords: Terapia Ocupacional; Comunicação Alternativa; Inclusão Escolar; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL